Clinical Applications of Personalized Medicine: A New Paradigm and Challenge - Di Sanzo, Mariantonia; Cipolloni, Luigi; Borro, Marina; La Russa, Raffaele; Santurro, Alessandro; Scopetti, Matteo; Simmaco, Maurizio; Frati, Paola (Current Pharmaceutical Biotechnology, 2017)
The personalized medicine is an emergent and rapidly developing method of clinical practice that uses new technologies to provide decisions in regard to the prediction, prevention, diagnosis and treatment of disease. A continuous evolution of technology and the developments in molecular diagnostics and genomic analysis increased the possibility of an even more understanding and interpretation of the human genome and exome, allowing a “personalized” approach to clinical care, so that the concepts of “Systems Medicine” and “System Biology” are actually increasing. The purpose of this study is to evaluate the personalized medicine about its indications and benefits, actual clinical applications and future perspectives as well as its issues and health care implications. A careful review of the scientific literature on this field that highlighted the applicability and usefulness of this new medical approach as well as the fact that personalized medicine strategy is even more increasing in numerous fields of applications.
Keywords: healthcare